Between public and private : politics, governance, and the new portfolio models for urban school reform - Bulkley, Katrina E.; Henig, Jeffrey R., 1951-; Levin, Henry M. (Cambridge, Mass. : Harvard Education Press, 2010)
This book examines an innovative approach to school district management that has been adopted by a number of urban districts in recent years: a 'portfolio management model', in which 'a central office overseas a portfolio of schools offering diverse organizational and curricular themes, including traditional public schools, private organizations, and charter schools.' This book examines crucial issues related to portfolio management, gauges both the promise and potential pitfalls of the model, considers important contexts for assessing these ambitious efforts to reform district management, and offers in-depth cases of four urban districts- Chicago, New York, Philadelphia, and New Orleans- that have pioneered this new model. -- from Back Cover.
Introduction : portfolio management models in urban school reform / Katrina E. Bulkley -- Portfolio management models and the political economy of contracting regimes / Jeffrey R. Henig -- Neoliberal school reform in Chicago? : Renaissance 2010, portfolios of schools, and diverse providers / David Menefee-Libey -- Strong vision, learning by doing, or the politics of muddling through? : New York City / Jonathan Gyurko and Jeffrey R. Henig -- One step back, two steps forward : the making and remaking of "radical" reform in Philadelphia / Katrina E. Bulkley, Jolley Bruce Christman, and Eva Gold -- A diverse education provider : New Orleans / Henry M. Levin, Joseph Daschbach, and Andre Perry -- Where's the management in portfolio management? : conceptualizing the role of urban school district central offices in implementation / Meredith I. Honig and Michael DeArmond -- A framework for designing governance in choice and portfolio districts : three economic criteria / Henry M. Levin -- Convergence or collision : portfolio districts, education markets, and federal education policy / Patricia Burch -- Disseminating and legitimating a new approach : the role of foundations / Sarah Reckhow -- Portfolio management models : from the practitioner's eyes / Josh Edelman -- Where public meets private : looking forward / Jeffrey R. Henig and Katrina E. Bulkley.
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Urban schools -- United States; Εκπαίδευση, Αστική -- Ηνωμένες Πολιτείες Αμερικής; Education, Urban -- Government policy -- United States; School improvement programs -- United States; Portfolio management -- United States; Portfolio management; School improvement programs; Urban schools; United States